Literature Survey on Energy Consumption Control for Wireless Mobile Ad-hoc Network (International Journal of Engineering and Computer Science, 2017)
Energy consumption control in wireless ad-hoc networks is a more difficult problem due to non availability of access point in network. A node can be both a data source and a router that forwards data for other nodes. There is no centralized entity such as an access point to control and maintain the power control mode of each node in the network. There are number of challenges offered by mobile adhoc network environment like limited power, route failure, synchronization, security etc. Nodes in the mobile ad-hoc network environment have limited battery power. Extra amount of energy is needed by router to forward and to relay packets. In this paper, literature survey is carried out on energy consumption issues for wireless ad-hoc network.